Manajemen Diri untuk Menurunkan Perilaku Tidak Aman Dalam Bekerja pada Pengemudi Bus Trans Jogja - Ika Zenita Ratnaningsih; Rahmat Hidayat (Universitas Islam Indonesia, 2010)
Unsafe work behavior as one cause of the occupational accidents still have high rates. Self management, one of type behavior based interventions, known as an intervention that is suitable for workers who work in solitary or low supervison working condition. The aim of this study is to determine the effect of self management intervention on reducing unsafe behavior at work. The subjects of this sutdy were 36 male Trans Jogja bus drivers. Subjects were divided into two groups, 19 drivers in the experimental group and 17 drivers in the control group. The experimental group received treatment that contain self management training followed by self monitoring for 2 weeks, whereas the control group didn't receive any treatment. The result of mixed anava indicate that self management intervention doesnt give significant effect to reduce unsafe behavior (F=0,208; p>0,05)Keywords: self-management, unsafe work behavior